Quitting the Boss? The Role of Manager Influence Tactics and Employee Emotional Engagement in Voluntary Turnover. (February 2018) - Reina, Christopher S.; Rogers, Kristie M.; Peterson, Suzanne J.; Byron, Kris; Hom, Peter W.
Employees commonly cite their managers' behavior as the primary reason for quitting their jobs. We sought to extend turnover research by investigating whether two commonly used influence tactics by managers affect their employees' voluntary turnover and whether employees' emotional engagement and job satisfaction mediate this relationship. We tested our hypotheses using survey data collected at two time points from a sample of financial services directors and objective lagged turnover data. Using multilevel path modeling, we found that managers' use of pressure and inspirational appeals had opposite effects on employee voluntary turnover and that employees' emotional engagement was a significant and unique mediating mechanism even when job satisfaction, the traditional attitudinal predictor of turnover, was also included in the path model. Our findings contribute to turnover research by demonstrating a relationship between specific managerial behaviors and employee turnover and shed light on a key mediating mechanism that explains these effects.